Demand-Response Application in Wastewater Treatment Plants Using Compressed Air Storage System: A Modelling Approach - Mattia Cottes; Matia Mainardis; Daniele Goi; Patrizia Simeoni (Energies, 2020)
Wastewater treatment plants (WWTPs) are known to be one of the most energy-intensive industrial sectors. In this work, demand response was applied to the biological phase of wastewater treatment to reduce plant electricity cost, considering that the daily peak in flowrate typically coincides with the maximum electricity price. Compressed air storage system, composed of a compressor and an air storage tank, was proposed to allow energy cost reduction. A multi-objective modelling approach was applied by analyzing different scenarios (with and without anaerobic digestion, AD), considering both plant characteristics (in terms of treated flowrate and influent chemical oxygen demand, COD, concentration) and storage system properties (volume, air pressure), together with the current Italian market economic conditions. The results highlight that air tank volume has a strong positive influence on the obtainable economic savings, with a less significant impact held by air pressure, COD concentration and flowrate. In addition, biogas exploitation from AD led to an improvement in economic indices. The developed model is highly flexible and can be applied to different WWTPs and market conditions.